Proteomic profiling of endorepellin angiostatic activity on human endothelial cells - Zoeller, Jason J (BioMed Central, 2008)
BACKGROUND: Endorepellin, the C-terminal domain V of the heparan sulfate proteoglycan perlecan, exhibits powerful and targeted anti-angiogenic activity on endothelial cells. To identify proteins involved with endorepellin anti-angiogenic action, we performed an extensive comparative proteomic analysis between vehicle- and endorepellin-treated human endothelial cells. RESULTS: Proteomic analysis of endorepellin influence on human umbilical vein endothelial cells identified five differentially expressed proteins, three of which (β-actin, calreticulin, and chaperonin/Hsp60) were down-regulated and two of which (vimentin and the β subunit of prolyl 4-hydroxylase also known as protein disulfide isomerase) were up-regulated in response to endorepellin treatment—and associated with a fold change (endorepellin/control) ≤ 0.75 and ≥ 2.00, and a statistically significant p-value as determined by Student's t test. CONCLUSION: The proteins identified represent potential target areas involved with endorepellin anti-angiogenic mechanism of action. Further elucidation as such will ultimately provide useful in utilizing endorepellin as an anti-angiogenic therapy in humans.